Genetic polymorphisms in the pathogenesis and course of Crohn’s disease - Gocel, Oliwia; Pendrasik, Karolina; Frąk, Weronika; Małecka-Wojciesko, Ewa (Medical Studies/Studia Medyczne, 2023)
Crohn’s disease is a chronic inflammatory disease that affects the full length of the digestive tract. The precise aetiology is still unknown, but genetic, environmental, and immunologic factors are involved. The aim of this article is to summarize the current susceptibility genes and gene polymorphisms involved in the disease pathogenesis and clinical course. In recent studies an association was found between FUT2, ATG16L-1, IL-10, TLR, and NOD2 gene mutations and Crohn’s disease. Each of them may affect the disease at a different stage of immune response, are involved in bacterial identification, or are related to bacterial dysbiosis. We present their effect of disease susceptibility, age of onset, severity, risk of surgery, and concomitant infections. Further research in this area may prove useful in early diagnosis, prognosis, and treatment of Crohn’s disease.